A STUDY ON THE ABILITY OF THE SECOND SEMESTER STUDENTS OF SMA WITAMA NATIONAL PLUS PEKANBARU IN WRITING NARRATIVE TEXTS - Sitio, Josua Suares; Eliwarti, Eliwarti; M. Syarfi, M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research investigates the ability of the second semester students of SMA Witama Nasional Plus Pekanbaru in writing a narrative text. The population of this research was the second semester students of SMA Witama Nasional Plus Pekanbaru in academic year of 2019/2020. There were 19 students who participate as the sample of this research. The students are tested using a writing test. The result of the test given was then classified into certain categories. The test results of 19 students shows that 5 students (26.32%) are in excellent category, 14 students (73.68%) are in good level. In addition, the average score of the students in writing a narrative text is 75.61. It means that the students’ ability in writing a narrative text was in the good level. Based on the tests, it can be concluded that the second semester students of SMA Witama Nasional Plus Pekanbaru already were in good ability to write a narrative text. Researcher recommended the students and other researchers to conduct similar research to get further information.Key Words: Ability, Writing, Narrative Text